The Effect of Problem Based Learning and Learning Motivation of Mathematical Problem Solving Skills of Class 5 Students at SDN 0407 Mondang - Arif Mahmuda Pohan; Asmin Asmin; Asih Menanti (BIRCU, 2020)
This study aims to: 1) find out whether students' mathematical problem solving abilities that are taught with problem based learning are better than students who are taught by direct learning. 2) find out whether the mathematical problem solving ability of students who have high learning motivation is better than students who have low learning motivation. 3) find out whether there is an interaction between learning and student learning motivation towards students' mathematical problem solving abilities. This study uses a quasi-experimental method with a 2x2 factorial design. The study population was fifth grade students (five) in the odd semester of the 2017/2018 Academic Year at SDN 0407 Mondang which consisted of two classes with a sample of 50 students. The class used as the sample of the experimental group is class V A with 25 students and the control class is class V B with 25 students. Thus the sample selection is done by total sampling technique. Data was collected by student achievement test and student motivation instrument. The collected data was processed statistically using a two-way variance (anava) analysis technique with a significance level of 0.05. The results showed that (1) There was an influence of problem-based learning methods on the mathematical problem solving ability of Class V students of SD Negeri 0407 Mondang 2017/2018 Academic Year; (2) There is an influence of student learning motivation on the mathematical problem solving ability of fifth grade students of SD Negeri 0407 Mondang for the Academic Year 2017/2018; and (3) There is an interaction between problem-based learning methods and students' motivation to the mathematical problem solving ability of students of Class V of SD Negeri 0407 Mondang 2017/2018 Academic Year. Practically, this study recommends that teachers use problem-based learning methods in mathematics learning and pay attention to the level of student motivation so that the learning design is adjusted to that motivation level. Theoretically, this study contributes to adding knowledge related to problem-based mathematics learning in elementary schools. Further studies can deepen studies related to the suitability of student characteristics with the selected learning method because these aspects are indicated as one of the key factors for student learning success.